PELAKSANAAN FUNGSI REKOMENDASI OMBUDSMAN REPUBLIK INDONESIA TERHADAP KEPALA DAERAH - Setiawan, Adam (Faculty of Law, Parahyangan Catholic University, 2020)
The author grapples with the issue of how Heads of Regional government respond to Ombudsman’s recommendations, suggesting correction of public service failures, and what are the legal repercussions if those regional government heads chose to disregard such recommendation. Relevant legal norms - identified from existing legal sources - shall be discussed. It is suggested that Heads of Regional Governments are under the legal obligation to heed the given recommendation and rectify the government error as proposed. In practice, recommendations can and have been on numerous times been ignored. Administrative sanctions, i.e. obligatory special re-training-education programs, in the case of failure to meet Ombudsman’s recommendation, has been dismissed with impunity by both the Ministry of Home Affairs and the Heads of Regional/Local government, by reason of political or legal considerations.